Hematological response in patients with paroxysmal nocturnal hemoglobinuria treated with C5-inhibitor - V. D. Latyshev; Z. T. Fidarova; R. V. Ponomarev; N. V. Tsvetaeva; E. A. Mikhaylova; E. A. Lukina; E. N. Parovichnikova (Онкогематология, 2024)
Background. Paroxysmal nocturnal hemoglobinuria is a rare clonal disease of the hematopoietic system, with the key manifestations of hemolytic anemia, a high thrombosis rate, and bone marrow failure. Despite the high efficacy of C5‑inhibitors in intravascular hemolysis cessation, a significant proportion of patients remain anemic. Causes of a sub‑optimal response may include C3‑mediated extravascular (intracellular) hemolysis, residual intravascular hemolysis, or bone marrow failure.Aim. To analyze the results of pathogenetic therapy in patients with paroxysmal nocturnal hemoglobinuria.Materials and methods. The study included 55 patients with paroxysmal nocturnal hemoglobinuria receiving complement C5 inhibitors for at least 6 months. Results. Suboptimal hematological response was observed in 31/55 (56 %) patients. The most common cause of anemia in the partial response group was C3‑mediated extravascular hemolysis in 8/10 (80 %), while bone marrow failure predominated (57 %) in the minor response group.Conclusion. The study showed a high frequency of suboptimal response to pathogenetic therapy and necessity of ac‑curate determination of leading cause of persistent anemia in order to modify therapy or switch to other drugs.